Clinical performance analysis and cost-utility analysis of a mobile cataract surgery service in a rural setting in Thailand - Mantapond Ittarat; Wanrudee Isaranuwatchai; Sunee Chansangpetch (AJO International)
Purpose: To evaluate a clinical performance and cost-effectiveness of a mobile cataract surgery service, specifically and separately for Phacoemulsification (Phaco) and extracapsular cataract extraction (ECCE) Design: A pre-post study with individual-level data Methods: Patients diagnosed with advanced cataracts underwent cataract surgery at a mobile cataract surgery service. Data on corrected distance visual acuity (CDVA), quality of life (QOL) assessed by EQ-5D-5L questionnaire, and cost were prospectively collected at and compared between baseline and 3 months after treatment. Linear regression was used to analyze the clinical performance, and a cost-utility analysis (CUA) was conducted to show the cost-effectiveness of the mobile service. Results: A total of 98 eyes from 98 patients had cataract surgeries, with 53 patients (54 %) undergoing Phaco techniques and 45 patients (46 %) undergoing ECCE techniques. For the total cohort, LogMAR CDVA changed from 1.88±0.59 to 0.23±0.23 (p < 0.001) with only one case of complication. Significant improvements of mobility and usual activities QOL scores, and utility values were demonstrated (all p < 0.001). Separate CUAs by technique with pre-post data showed that patients with Phaco gained 4.93 QALYs and costed approximately THB 18,800 (USD 535) and patients with ECCE gained 5.45 QALYs with the cost of THB 14,400 (USD 412). Conclusions: A mobile cataract surgery service is effective in improving vision and QOL with a low complication rate. The CUAs showed that both Phaco and ECCE could be cost-effective. Implementing such services in rural areas could be a strategy to increase effective cataract surgery coverage.